PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MASYARAKAT MENJADI PELANGGAN PDAM SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Mursyid Mursyid; Muhammad Fatkhurohman Albashori (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The purpose of this study was to determine 1) the influence of the product on the community decision to become a customer of PDAM Sleman DIY, 2) the influence of price on the community decision to become a customer of PDAM Sleman DIY, 3) the influence of distribution on the community decision to become a customer of PDAM Sleman DIY, 4) the effect of promotion on the community decision to become a customer of PDAM Sleman DIY, and 5) the effect of the curious mix consisting of product, price, distribution and promotion simultaneously on the community decision to become a customer of PDAM Sleman DIY. The results of the study concluded that 1) The product has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t arithmetic value of 6.471, 2) Price has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t-count value of 3.157, 3) Distribution has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the t value of 7.033, 4) Promotion has a significant influence on customer decisions of PDAM Sleman. This is evidenced by the value of t count of 5.173, and 5) Product, price, distribution and promotion together have a significant influence on customer decisions of PDAM Sleman. This is evidenced by the calculated F value of 74,316.